PERBEDAAN ASUPAN DAN STATUS GIZI PADA PASIEN STROKE HEMORAGIK DAN NON HEMORAGIK DI RSUD PROF. DR. MARGONO SOEKARJO - Deviana Ayushinta Sani Siregar; Saryono Yono (Jurnal Gizi dan Pangan Soedirman, 2018)
Background: Stroke is a disease of the brain in form of nerve dysfunction locally or globally, appears in sudden, progressive, and fast. World Health Organization (WHO) estimates that the stroke caused 5.7 million deaths in the world. Stroke can be caused by bleeding or clotting. The wide of diameter of the lesions in patients with hemorrhagic stroke increased 20% compared with the extent of the lesion in patients with ischemic stroke. Prevalence of malnutrition significantly more general in hemorrhagic stroke (62%) than ischemic stroke (25%). The impact of malnutrition in stroke patient can increase mortality after three months onset of stroke. Methods: The research conducted in Prof. Dr. Margono Soekarjo hospital, using a cross sectional study program and using purposive sampling technique. The total of sample used is 44 people, consisting of a group of non-hemorrhagic stroke and hemorrhagic stroke. The analysis of data is using t independent bivariate test. Results: The group average intake levels of hemorrhagic stroke is lower than ischemic stroke. According to the anthropometry index MUAMC and BMI, the hemorrhagic stroke group average is lower than the ischemic stroke. Conclusion: According to the result of statistic analysis, the researcher did not find a significant difference on the intake of nutrient and nutritional status in hemorrhagic stroke and ischemic stroke patient.